Non-pharmacological analgesia strategies in adult and elderly endovascular procedures: a scoping review - Kauanny Vitoria Gurgel dos Santos; Mayara Araujo Rocha; Joyce Karolayne dos Santos Dantas; Sara Cristina Matias de Araújo; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: To identify the main non-pharmacological analgesia strategies used in clinical practice in adult and elderly endovascular procedures. Methods: scoping review, undertaken in July 2021, on 12 national and international data sources. The recommendations of the JBI and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews checklist were followed. Thirteen studies were selected to compose the sample, with no time or language cut-off. Results: the main non-pharmacological strategies found were cold compress, use of music, and reflexology. The most prevalent procedures were coronary angiography, peripheral venous catheterization, and femoral catheter removal. Pain measurement by Visual Numeric Scale and Visual Analog Scale described pain reduction in adults and elderly. Conclusions: the main non-pharmacological strategies found were cold compress, use of music, and reflexology, which reduce pain in adults and the elderly.